The Effectiveness of Family Therapy on Self-Forgiveness and Quality of Life in Self-Harming Adolescents - Moradi, Elham; Sabbagh Torbati, Hosein; Jabbarizadegan, Shaghayegh; Kazlou, Hannaneh; Alipour, Sedigheh (Shahroud Journal of Medical Sciences, 2024)
Background: The objective of this study was to examine the efficacy of family therapy methods in enhancing self-forgiveness and overall quality of life among adolescents engaging in self-harm. Methods: This study utilized a semi-experimental approach, employing a pre-test, post-test, and follow-up design spanning over three months. There were three sets of participants, including two experimental groups made up of both girls and boys, as well as a comparison group. The data collection period for this research spans from July to November 2023. The sample for the study included 60 individuals who were chosen through purposeful sampling and assigned randomly to two experimental groups and a control group, with each group comprising 20 participants. The experimental groups consisted of a male group of 16 individuals and a female group of 14 individuals, who underwent seven sessions lasting 90 minutes twice a week. On the other hand, the control group, composed of 17 participants, did not receive any intervention. Research tools included the Heartland Forgiveness Scale (HFS) and the World Health Organization Quality-of-Life Scale (WHOQOL-BREF). The method of data analysis was performed using Kruskal-Wallis H, ANOVA, MANCOVA, and Bonferroni post hoc tests and Tukey HSD at a significance level of 0.05 in SPSS.27 software. Results: The results suggest that there was a notable difference in the levels of self-forgiveness observed during the post-test and follow-up stages(P<0.05). Moreover, there was no notable difference in terms of psychological health and social relationships between the two groups of self-harming girls and boys (P>0.05). Conclusion: The findings of the current research indicate that family therapy has a positive impact on self-forgiveness, mental well-being, and social connections.